Adaptasi Visual Pare sebagai Desain Ragam Hias Batik Karawang - Laksitarini, Ike Niken; Sunarya, Yan Yan; Tresnadi, Chandra (Visualita Jurnal Online Desain Komunikasi Visual, 2019)
Batik is one from of art and has become an acon of Indonesian indigenous culture and Batik Karawang is one of them. Its exixtence is not yet as popular as batik from other regions. However, several efforts have been made by cultural observer Karawang Regency and related agencies in introducing and developing Batik Karawang. Geographically, Karawang Regency is an area that has extensive agricultural land. Even though it is a coastal area, the agricultural land in Karawang Regency is an area that is able to produce good quality rice, this is because Karawang Regency is located adjacent to the Citarum River which functions to irrigate all agricultural land in Karawang Regency. So it is not surprising that the batik ornaments created are dominated by rice plants or bitter melon as the main decorative variety. Pare in Indonesian means rice, while sagendeng means one tie. The use of ornamental names that refer to the natural and cultural elements of the Karawang district has symbolic meaning that refers to the ideas and expectations of the local community for good. From the results of the study obtained a relationship or relationship that the aesthetic elements contained in the Karawang Batik decoration is a form of visual adaptation (culture) of Karawang regency society which is correlated with the discovery of the name kekembangan on Sundanese terms found in Lalakaon ti Karawang script. This study aims to unravel the form of adaptation to the Pare ornament. This research is expected to provide insight for the general public regarding the existence of Batik Karawang so that it can develop the potential and economy of UMKM (Usaha Mikro Kecil dan Menengah) on Karawang regency. The type of research used is qualitative research with a descriptive approach. From the results of the study it was found that most of the basic patterns of Karawang Batik motifs were ridiculous. Ceplokan is one of the batik motifs which consists of repetition of the ceplok pattern unit so that as a whole it forms a single unit.